Simulation of complex regional technology innovation ecosystem under resource constraints. (2016) - Wei, Tie; Zhu, Zhiwei; Lei, Lei; Cheek, Ron
The development of a regional technological innovation ecosystem (RTIE) under resource constraints is uncertain and complex. Based on the complex systems theory, this paper discusses the evolution of RTIE through modelling and the simulation of a multi-agent system (MAS). Specifically, it proposes a theoretical model of RTIE under innovation resource constraints and explains the adaptive changes of the RTIE. It operationalises the concepts into dimensions of the quantified variables. Also, it uses the swarm software to simulate the evolution of the RTIE under innovation resource constraints. The simulation model incorporates an environment of innovation resource constraints and various situations under the control policies. The results show resource agents will gradually gather around enterprise agents. Enterprise and resource agents will be distributed differently in the regional space. The different control agent's actions may also lead to different evolution results. The study provides some theoretical foundations for future research in RTIE's evolution and regulation.